1994
DOI: 10.1002/bjs.1800810535
|View full text |Cite
|
Sign up to set email alerts
|

Influence of total colectomy on serum antineutrophil cytoplasmic antibodies in inflammatory bowel disease

Abstract: Perinuclear antineutrophil cytoplasmic antibodies (pANCAs) have previously been demonstrated in patients with various forms of vasculitis and more recently in those with inflammatory bowel disease (IBD) by an indirect immunofluorescence technique. Sera from 194 patients were tested for pANCAs: 101 with ulcerative colitis (43 with varying grades of disease severity, 19 after subtotal colectomy, 39 following restorative proctocolectomy), 40 with Crohn's disease, five with indeterminate colitis, 24 patients witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
4

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(18 citation statements)
references
References 19 publications
0
14
0
4
Order By: Relevance
“…Initial studies in the 1990s examining the correlation between pANCA and pouchitis produced conflicting results. Some studies have shown a correlation between pANCA presence and the development of pouchitis,124–128 while others have not 88, 198–202. However, these early studies were retrospective in design and included relatively small sample sizes.…”
Section: Disease Stratification and Prediction In Ucmentioning
confidence: 99%
“…Initial studies in the 1990s examining the correlation between pANCA and pouchitis produced conflicting results. Some studies have shown a correlation between pANCA presence and the development of pouchitis,124–128 while others have not 88, 198–202. However, these early studies were retrospective in design and included relatively small sample sizes.…”
Section: Disease Stratification and Prediction In Ucmentioning
confidence: 99%
“…Several studies showed that the presence of the diseased organ is not necessary for the presence of ANCA in the serum from patients with UC. ANCA were detected after colectomy [ 58–60], although in some studies titres declined [ 61]. An association was reported between ANCA and the development of pouchitis in patients with UC who underwent surgery [ 60, 62, 63], but more recent studies failed to confirm this association [ 64, 65].…”
Section: Clinical Significance Of Anca In Ibdmentioning
confidence: 99%
“…The pANCA-positive status usually remains stable in human patients, even with clinical improvement. 15 In a study of ulcerative colitis patients by Patel et al, 22 pANCA-positive status was stable for 2 years after initiation of therapy. It would be unusual for the pANCA status in a patient with Crohn's disease to change from negative to positive.…”
Section: Discussionmentioning
confidence: 97%